A Financial Pillar Rooted in Spiritual Values for Community Welfare : Islamic Economics - Fusthathul Nur Sasongko; Anisatul Maghfiroh (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
Islamic economics serves as a comprehensive financial system rooted in spiritual values, emphasizing justice, equity, and social welfare. This study aims to explore the principles, benefits, and challenges of implementing Islamic economics in contemporary financial systems. The research adopts a qualitative approach through an extensive literature review, analyzing scholarly articles, books, and case studies from 2018 to 2024. The findings reveal that Islamic economics, through its prohibition of interest (riba) and speculative activities (gharar), alongside the promotion of profit-sharing mechanisms (mudharabah and musyarakah), offers a more ethical and sustainable alternative to conventional financial systems. Key instruments such as zakat and waqf significantly contribute to poverty alleviation and wealth redistribution, enhancing social welfare. However, the study identifies challenges such as limited public awareness, inadequate regulatory frameworks, and competition with conventional systems. The research concludes that Islamic economics provides a robust framework for addressing global economic inequalities and fostering financial stability. To optimize its implementation, collaborative efforts from governments, financial institutions, and society are crucial. This study contributes to the growing body of knowledge by highlighting the transformative potential of Islamic economics and its capacity to achieve holistic and sustainable development.